Relationship between Learning Resources and Students’ Learning Methods on Biology Student Learning Outcomes in XI MIPA Class - Sari, Mustika; Utami, Nur Rahayu; Isnaeni, Wiwi (FMIPA UNNES, 2020)
The achievement of student learning outcomes is influenced by various factors, such as learning resources and ways of learning. The purpose of this study is to determine the relationship between learning resources and learning outcomes; know the relationship between how to learn and the learning outcomes; and know the relationship between learning resources and ways of learning on the learning outcomes. The sample in this study was 108 students. The independent variables in this study are learning resources (X1) and ways of learning (X2). The dependent variable in this study is learning outcomes (Y). The data collection method used a questionnaire and documentation. Data analysis in this study used descriptive percentages, multiple linear regression, t test and F test. The results showed that the analysis of multiple linear regression obtained equation: Y = 52.078 + 0.224X1 + 0.203X2. Partially, the influence of learning resources on learning outcomes was 43.3%, while the influence of learning methods was 42.6%. Simultaneously, learning resources and ways of learning influenced the learning outcomes by 47.3%, with SE (X1) = 24.6%, and SE (X2) = 22.7%. Based on the results of the analysis, it can be concluded that learning resources and ways of learning significantly influenced learning outcomes, both partially and simultaneously. In this study, learning resources had a greater influence on learning outcomes compared to the of way of learning on learning outcomes. Thus, schools need to optimize all learning resources both in their existence and utilization, and students need to improve their way of learning in order to get optimal learning outcomes.